2002
DOI: 10.1029/2001gl014291
|View full text |Cite
|
Sign up to set email alerts
|

HF radar observations of Pc5 ULF pulsations driven by the solar wind

Abstract: [1] We present HF radar observations of Pc5 field line resonances in the post-midnight Antarctic ionosphere on April 28/29 1997. Simultaneous oscillations were seen in the solar wind parameters observed by WIND. The spectra of both sets of data show peaks near 1.3 mHz, 1.9 mHz, 2.7 mHz and 3.3 mHz. The data were bandpass filtered and a complex demodulation technique applied to calculate the instantaneous energy flux in the solar wind in each band and hence the power incident on the front of the magnetosphere 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
78
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(82 citation statements)
references
References 20 publications
4
78
0
Order By: Relevance
“…Prikryl et al (1998Prikryl et al ( , 2002 also suggested a direct link between Alfvénic solar wind fluctuations and Pc5 field line resonance observations observed equatorward of the cusp on closed field lines. Stephenson and Walker (2002) similarly presented an analysis of upstream solar wind data and SuperDARN velocity data demonstrating that, at least on occasion, common spectral peaks are observed in both, suggesting direct driving of magnetospheric field line oscillations by wave activity in the solar wind.…”
Section: Externally Driven Wavesmentioning
confidence: 99%
“…Prikryl et al (1998Prikryl et al ( , 2002 also suggested a direct link between Alfvénic solar wind fluctuations and Pc5 field line resonance observations observed equatorward of the cusp on closed field lines. Stephenson and Walker (2002) similarly presented an analysis of upstream solar wind data and SuperDARN velocity data demonstrating that, at least on occasion, common spectral peaks are observed in both, suggesting direct driving of magnetospheric field line oscillations by wave activity in the solar wind.…”
Section: Externally Driven Wavesmentioning
confidence: 99%
“…[3] Recent work has proposed that discrete compressional MHD oscillations [Stephenson and Walker, 2002;Eriksson et al, 2006] and Alfvenic oscillations [Prikryl et al, 1998] in the solar wind may directly drive magnetospheric FLRs. Other studies have shown similarities between individual discrete solar wind compressional oscillations and global magnetospheric pulsations observed in geosynchronous magnetic fields [Kepko and Spence, 2003] and in low latitude ground based magnetometer measurements [Villante et al, 2007].…”
Section: Introductionmentioning
confidence: 99%
“…Other ways of exciting the cavity include the mechanism of Mann et al (1999), who showed how the overreflection mechanism could extract energy from the shear motion at the boundary. Observations of some events show correlation with coherent waves in the solar wind (Kepko et al, 2002;Stephenson and Walker, 2002). These can excite the cavity modes (Walker, 2002) and hence excite the field line resonance.…”
Section: Source Mechanismsmentioning
confidence: 99%
“…When observed in the meridian plane the oscillation appears to be standing. There is generally phase advance in the azimuthal direction, which is characterized by the azimuthal wave number m. Various sources have been identified such as Kelvin-Helmholtz oscillations at the magnetopause (Southwood, 1968), excitation of cavity or waveguide modes (Kivelson and Southwood, 1985;Samson et al, 1992), direct control by oscillations in the solar wind (Stephenson and Walker, 2002), and more recently fluctuating field-aligned currents in the auroral zone (Pilipenko et al, 2016). Pulsations can also be generated by drift-bounce resonance with ring current particles (Dungey, 1965).…”
Section: Introductionmentioning
confidence: 99%